CHANGES IN THE CYTOKINE STATUS WITH STABLE ANGINA - E. K. Gordeeva; A. H. Kade (Медицинский вестник Юга России, 2016)
This review summarizes the current evidence on the role of cytokines in the pathogenesis of ischemic myocardial damage. It described the important role of inflammation in the development of coronary heart disease. The role of individual cytokines in the pathogenesis of coronary artery disease and the most frequent forms of it - angina. It is shown that in patients with coronary heart disease progression of the disease is due to an imbalance in cytokine system, elevated pro-inflammatory cytokines (TNF, IL-1β, IL-6). Anti-inflammatory cytokines (IL-4, IL-10) inhibit the secretion of proinflammatory cytokines by limiting excessive intensity of the immune response. Revealed increasing levels of TGF-β1 as a key cytokine that promotes the development of fibrosis in the wall of the heart and blood vessels. The interrelation between improving markers of inflammation and the development of coronary heart disease, the predictive value of these markers of inflammation in patients with stable coronary heart disease: angina of effort of different functional classes.